Pregnancy outcomes status of wives of veterans with mental disorders in Mazandaran 1389 - A. Hafezian; G. Azgoli (Afarand Scholarly Publishing Institute, 2011)
BACKGROUND AND PURPOSE : In Iran, research on veterans and spouses of the mental, emotional and psychological effects are largely paid for them. Many foreign studies, the effects of war on soldierschr('39') wives pregnancy outcomes that have participated in the Iran-Iraq war Zdv conflicting results have been obtained. . The impact of war on veterans and their spouses and the possibility of damage caused by impact damage on the status and outcome of pregnancy in this group of women, and this research has been done in Iran, The study of pregnancy and its impact on veterans and their spouses have been flowing this province. METHOD: this descriptive study was performed on 182 wives of veterans suffering from psychiatric problems, which were chosen randomly in 1389 in Mazandaran. The data were collected by researcher-made questionnaire with content validity and test-retest reliability at two times and the correlation coefficient of 92 / 0 and were analyzed by the software SPSS 17. RESULTS: The findings suggest that 7.19% of pregnancies were unwanted, 5.22% with high risk, 2.13% with unintentional abortion, 2.8% with deliberate abortion and 3.3% with ectopic pregnancy. and the results of the pregnancies include 4.4% stillbirth, 7.7% preterm labor, 3.19% low birth weight and 3.3% of births has been associated with congenital malformations. CONCLUSION: The index and comparing it with existing global and regional indicators, status and appears to be the result of pregnancy (the study factor) in the veteranschr('39') wives and smooth, not negative, However Comparative studies with control groups, also check the status and pregnancy outcome in other groups veterans community, is recommended.